Antibiotic Adjuvants – A Review Article (Central Medical College Journal, 2025)
Antibiotic resistance (AR) has emerged as a critical global health challenge, affecting both natural and synthetic antibiotics. The search for new, more effective antibiotics is costly and difficult, making alternative strategies, such as antibiotic adjuvants, an important area of focus. This review explores the potential of adjuvants in combating AR. Antibiotic resistance occurs through mechanisms like (i) antibiotic inactivation via enzymatic modification or breakdown, (ii) reduced antibiotic uptake due to increased efflux, and (iii) modification of the antibiotic target site. These mechanisms present opportunities for adjuvant drug development, targeting proteins or enzymes involved in resistance. Recent research highlights broad-spectrum antibiotic adjuvants and hybrid approaches, aiming to inhibit key resistance mechanisms, such as β-lactamase enzymes and efflux pumps, or disrupting bacterial signaling and response systems. Other adjuvants enhance antibiotic uptake, prevent modification of antibiotics or their targets, or target non-essential bacterial processes like cell wall synthesis. While progress is being made, the ongoing race between developing new antibiotic therapies and microorganisms acquiring resistance mechanisms remains a significant challenge.Central Medical College Journal Vol 8 No 2 July 2024 Page: 87-101